2017
DOI: 10.1111/jen.12413
|View full text |Cite
|
Sign up to set email alerts
|

Female sex pheromone of Athetis lepigone (Lepidoptera: Noctuidae): Identification and field evaluation

Abstract: Athetis lepigone has been recorded in many countries in Europe and Asia, but it had never been documented as an agricultural pest until 2005. For the purpose of using the sex pheromone to control this pest, we conducted a study to identify the sex pheromone of A. lepigone by gas chromatography with an electroantennographic detector (GC-EAD) and GC coupled with mass spectrometry (GC/MS) analyses. Three pheromone candidates were detected by GC-EAD analysis in the extracts of the female sex pheromone gland, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Subsequently, we analyzed the relative binding affinities of purified AlepOBP6 protein to 20 different ligands using 1‐NPN as a fluorescent probe, including two sex pheromones ( Z 7‐12:Ac and Z 9‐14:Ac) from female A. lepigone 32 and 18 host plant (maize) volatiles 46–49 (Figure 2B–D and Table 1). The results showed that AlepOBP6 could bind to the sex pheromones with K i values of 21.21 ± 2.12 μ m ( Z 7‐12:Ac) and 14.50 ± 1.44 μ m ( Z 9‐14:Ac).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we analyzed the relative binding affinities of purified AlepOBP6 protein to 20 different ligands using 1‐NPN as a fluorescent probe, including two sex pheromones ( Z 7‐12:Ac and Z 9‐14:Ac) from female A. lepigone 32 and 18 host plant (maize) volatiles 46–49 (Figure 2B–D and Table 1). The results showed that AlepOBP6 could bind to the sex pheromones with K i values of 21.21 ± 2.12 μ m ( Z 7‐12:Ac) and 14.50 ± 1.44 μ m ( Z 9‐14:Ac).…”
Section: Resultsmentioning
confidence: 99%
“…One of these novel approaches is based on understanding the mechanisms of insect olfaction that may lead to strategies disrupting host plant detection and other olfactory behaviors, thereby allowing insect populations to be controlled. We previously identified two female sex pheromones of A. lepigone , ( Z )‐7‐dodecenyl acetate ( Z 7‐12:Ac) and ( Z )‐9‐tetradecadienyl acetate ( Z 9‐14:Ac), 32 and 28 OBP genes, including ABPX (AlepOBP6), which showed male antennae‐biased expression, indicating that AlepOBP6 may be involved in some behaviors associated with males, such as recognition of female sex pheromones and host volatiles 33 . In this study, we further investigated the olfactory function of AlepOBP6 in A. lepigone , and binding affinities to two sex pheromones and 18 maize volatiles were examined using a fluorescence competitive binding approach.…”
Section: Introductionmentioning
confidence: 99%
“…As a newly invasive pest in China, S. frugiperda shares pheromone components with some local moth species. Athetis lepigone and Mythimna loreyi share the same pheromone components, Z 9‐14:Ac and Z 7‐12:Ac with S. frugiperda and have similar component ratios (Takahashi et al ., 1980; Yan et al ., 2018). To avoid cross‐specific attraction and improve monitoring accuracy, the pheromone synergists and antagonists of these species need to be further developed.…”
Section: Discussionmentioning
confidence: 99%
“…The development of novel green behavioral inhibitors based on olfactory genes has become a hot spot research field for pest control (Pelosi et al ., 2018; Caballero-Vidal et al ., 2021). In order to fully understand the concept of insect chemical communication, we have recently identified two female sex pheromone of A. lepigone as (Z)-7-dodecenyl acetate (Z7-12:Ac) and (Z)-9-tetradecenyl acetate (Z9-14:Ac) with a ratio of 1:5 by analyzing the extracts of the female sex pheromone gland (Yan et al ., 2018), and obtained three antennae-enriched PBP genes (AlepPBP1-3) in A. lepigone by antennal transcriptome analysis (Zhang et al ., 2017). Afterward, we expressed and purified the recombinant AlepPBP1 protein in a prokaryotic expression system.…”
Section: Introductionmentioning
confidence: 99%